Formaldehydes in Feed and Their Potential Interaction With the Poultry Gastrointestinal Tract Microbial Community–A Review - Ricke, Steven C.; Richardson, Kurt; Dittoe, Dana K. (Frontiers in Veterinary Science, 2019)
As antibiotics continue to be phased out of livestock production, alternative feed amendments have received increased interest not only from a research standpoint but for commercial application. Most of the emphasis to date has focused on food safety aspects, particularly on lowering the incidence of foodborne pathogens in livestock. Several candidates are currently either being examined or are already being implemented in commercial settings. Among these candidates are chemical compounds such as formaldehyde. Formaldehyde has historically been used to inhibit Salmonella in feeds during feed processing. Currently, there are several commercial products available for this purpose. This review will cover both the historical background, current research, and prospects for further research on the poultry gastrointestinal tract and feeds treated with formaldehyde.